Characteristics and Treatment Process of Wastewater in a Nylon Fabric Dyeing Plant - Ali, MS; Ahmed, S; Khan, MMS (Journal of Chemical Engineering, 2010)
Journal of Chemical Engineering Vol.ChE 23 1995-2005